Analysis of survival impact factors in heart transplant patients with modified donor hearts preservation method - Changdong Zhang; Yucheng Zhong; Yixuan Wang; Mei Liu; Xiaoke Shang; Nianguo Dong (BMC Cardiovascular Disorders)
Abstract Objective This study aimed to investigate the impact of factors on overall survival in heart transplant patients with modified donor hearts for cardiac protection, considering different preservation solutions and donor types. Methods A total of 834 heart transplant patients who underwent surgery between September 2008 and June 2021 were included in this retrospective study. Clinical data, including demographic information, diagnostic classifications, donor-related factors (such as donor type, cause of death, age, graft ischemic time, and preservation method), and surgical interventions, were collected. Cox proportional hazards models were utilized for univariate and multivariate analyses to identify prognostic factors for overall survival. Results The overall survival rate at 5 years post-transplantation was 71.9%, with a 10-year overall survival rate of 68.1%. Univariate analysis revealed that the cardiac tumors diagnostic category, presence of intra-aortic balloon pump (IABP), utilization of extracorporeal membrane oxygenation (ECMO) and continuous renal replacement therapy (CRRT), recipient age of 60 or older, and donor age of 45 or older were associated with poorer overall survival (p < 0.05). However, specific diagnostic classifications, donor cause of death, recipient body mass index (BMI), graft ischemic time, donor type (DCD vs. DBD), and preservation method (HTK vs. St. Thomas solution) did not show significant associations with overall survival (p > 0.05). Multivariate analysis confirmed that the cardiac tumors diagnostic category, recipient age of 60 or older, cardiopulmonary bypass time ≥ 130 min, and the use of CRRT and ECMO were independent predictors of shorter overall survival (p < 0.05). Conclusion This study highlights the significant impact of diagnostic classifications, recipient age, bypass time, and interventions on the overall survival of heart transplant patients with modified donor hearts preservation method. Patients classified as cardiac tumors those aged 60 or older, and those requiring longer bypass time or postoperative interventions such as CRRT and ECMO exhibited worse overall survival outcomes. These findings contribute to a better understanding of factors influencing survival outcomes in heart transplant patients with modified donor hearts preservation method and may have implications for optimizing patient selection and post-transplant management strategies. However, the retrospective nature of the study and the lack of data on certain variables, such as immunosuppressive regimens and post-operative care protocols, represent limitations that may affect the generalizability of the findings. Clinical trial number Not applicable.